The resilience handbook :Approaches o sterss and trauma - Kent, Martha(editor); Davis, Mary C.(editor); Reich, John W.,(editor) (New York Routledge, 2014)
"How are people and communities able to prevail despite challenge? What helps them bounce back from adversity and even grow in knowledge and understanding? And can this resilience be taught? During the past decade, exciting scientific advances have shed light on how resilience operates from neurons to neighborhoods. In The Resilience Handbook, experts in the science of resilience draw on human and animal research to describe the process of resilience and follow its course as it unfolds both within individuals and in social networks. Contributors also highlight the promise of new interventions that apply what we know about resilience processes to bolster positive health, and raise some of the pressing questions and issues for the field as it matures." --
1. Seeking the loss in the ancestral genesis of resilience, depression, and addiction / Jaak Panksepp -- 2. The role of predictive and reactive biobehavioral programs in resilience / Mattie Tops ... [et al.] -- 3. Approach/engagement and withdrawal/defense as basic biobehavioral adaptations: resilient transcendence of a popular duality / Martha Kent -- 4. Introduction to allostasis and allostatic load / Greta B. Raglan and Jay Schulkin -- 5. The automatic basis of resilience: adaptive regulation of affect and cognition / Susanne Schwager and Klaus Rothermund -- 6. The regulatory power of positive emotions in stress: a temporal-functional approach / Christian E. Waugh -- 7. Responding to trauma and loss: an emotion regulation perspective / Matthew Tyler Boden ... [et al.] -- 8. Music as an agent of resilience / Donald A. Hodges -- 9. Oxytocin and attachment facilitate a shift from seeking novelty to recognizing and preferring familiarity: the key to increasing resilience? / Mattie Tops ... [et al.] -- 10. Social touch and resilience / Mary H. Burleson and Mary C. Davis -- 11. Empathy and resilience in a connected world / Grit Hein -- 12. An attachment perspective on resilience to stress and trauma / Mario Mikulincer and Phillip R. Shaver -- 13. Using the caregiver system model to explain the resilience-related benefits older adults derive from volunteering / Stephanie L. Brown and Morris A. Okun -- 14. Resilience is social, after all / Alex J. Zautra -- 15. Developmental social factors as promoters of resilience in childhood and adolescence / Bekh Bradley ... [et al.] -- 16. Behavioral activation as a treatment for depression: theory, neurobiologic effects, and potential linkages to resilience / Gabriel S. Dichter ... [et al.] -- 17. Resilience training for action and agency to stress and trauma: becoming the hero of your life / Martha Kent and Mary C. Davis -- 18. Different strokes: empathy, individual characteristics, and helping / Alicia J. Hofelich and Stephanie D. Preston -- 19. Forgiveness interventions and the promotion of resilience following interpersonal stress and trauma / Nathaniel G. Wade, Jeritt R. Tucker, and Marilyn A. Cornish -- 20. Resilience interventions with a focus on meaning and values / Crystal L. Park and Jeanne M. Slattery -- 21. The skills training in affective and interpersonal regulation (STAIR) narrative model: a treatment approach to promote resilience / Christina M. Hassija and Marylene Cloitre -- 22. Promoting resilience after trauma: clinical stimulation of the Oxytocin system / Jessie L. Frijling ... [et al.]
Keywords: Resilience (Personality trait); Stress (Psychology)